VOCABULARY KNOWLEDGE DEVELOPMENT AND GENDER DIFFERENCES IN A SECOND LANGUAGE - Agustín Llach, María Pilar; Terrazas Gallego, Melania (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Previous research on vocabulary choice and acquisition from varied perspectives has shown that gender differences in EFL are relevant. However, studies in the area of L2 vocabulary size development concerning sex at different ages and educational stages have either revealed indefinite results or have been scarce, especially in the context of primary education. This study attempts to compensate for this paucity. We examined the importance of gender in receptive vocabulary size acquisition for 176 (94 males and 82 females) young Spanish students of EFL. They answered the 2000 word frequency-band from the receptive version of the VLT (Schmitt, Schmitt, & Clapham, 2001 version 2) over the 4th, 5th ,and 6th grades of primary education and the 1st, 2nd and 3rd years of secondary education (grades 4 to 9). Results proved that males and females increased their receptive knowledge of English words across grades and that their results showed highly significant differences in vocabulary size from one year to the next. Furthermore, learners increased their vocabulary knowledge in a linear way, although there was a tendency to show a significant gain in the last period tested. Finally, size differences in the mean scores of male and female learners were non-existent. In spite of these findings, female learners showed higher vocabulary gains than males for the first three intervals. For the last two intervals, this tendency reversed and male learners were found to incorporate more new words into their lexicons than their female peers. Resumen Diversas investigaciones previas sobre elección de vocabulario y adquisición de vocabulario han demostrado que las diferencias de género son relevantes en el aprendizaje de inglés como lengua extranjera. Sin embargo, otros estudios en el área del desarrollo léxico en la L2 obtienen resultados poco concluyentes en lo concerniente a las diferencias de género a lo largo de varias edades y contextos educativos. Los estudios son especialmente escasos en el contexto de educación primaria. El presente estudio pretende compensar dicha escasez. Se examina la importancia del género en el vocabulario receptivo de 176 aprendices españoles de inglés, 94 de ellos hombres y 82 mujeres. El test de las 2.000 palabras más frecuentes del ingles (Schmitt, Schmitt and Clapham 2001, version 2) se usó como instrumento de recogida de datos en 4º, 5º, 6º de primaria y 1º, 2º, y 3º de secundaria. Los resultados revelan que tanto hombres como mujeres aumentaron su repertorio léxico de manera significativa de un año escolar al siguiente. Este incremento léxico es linear, es decir, se aprende un número similar de palabras cada año, aunque hay una tendencia a un incremento significativamente mayor en el último intervalo evaluado. Finalmente, vemos que no existen diferencias significativas en el tamaño de vocabulario receptivo de hombres y mujeres, aunque las mujeres muestran incrementos mayores en los tres primeros intervalos. En el último, esta tendencia se invierte y los varones incorporan más palabras nuevas a su lexicón que las mujeres.